2018
DOI: 10.1111/tmi.13137
|View full text |Cite
|
Sign up to set email alerts
|

Disease characteristics and treatment of patients with diabetes mellitus attending government health services in Indonesia, Peru, Romania and South Africa

Abstract: DM patients in government clinics in four LMIC with considerable growth of DM have insufficient glycaemic control, frequent macrovascular and other complications, and insufficient preventive measures for cardiovascular disease. These findings underline the need to identify treatment barriers and secure optimal DM care in such settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
1
10
0
2
Order By: Relevance
“…Also, hypertension was common but often untreated. These figures are in line with significant gaps in management of DM in general that we found in these same settings [36].…”
Section: Discussionsupporting
confidence: 88%
“…Also, hypertension was common but often untreated. These figures are in line with significant gaps in management of DM in general that we found in these same settings [36].…”
Section: Discussionsupporting
confidence: 88%
“…However, diabetes prevention and improving diabetes management in low-income settings have both proved very challenging. The latter has substantial resource implications and requirements for training many health care providers, given the large numbers of patients with poorly managed diabetes [82,84]. A third TB prevention strategy could be latent tuberculosis infection (LTBI) screening and preventive therapy in people with diabetes; modern treatment regimens (e.g., 3HP) are shorter and simpler than previously used 6-9 months of isoniazid, making this approach more feasible.…”
Section: Control Of Diabetes-associated Tuberculosis At a Population Levelmentioning
confidence: 99%
“…Socio-economic status and the level of education are perhaps the factors most correlated with the incidence of DM in South Africa. A recent epidemiological study reported that economic status was the most important factor in the development of DM (Soetedjo et al, 2018 A correlation between ethnicity and the prevalence of DM is also evident. A higher than average incidence of morbidity and mortality from DM has been reported in black South African populations compared with other South African ethnic groups (Erasto et al, 2005).…”
Section: An Overview Of Diabetes Mellitus In South Africamentioning
confidence: 99%